SMARCA4 as a support for the differential diagnosis of poorly differentiated lung carcinomas - Panozzi, Martina; Alì, Greta; Proietti, Agnese; Melfi, Franca; Zirafa, Carmelina C.; Lucchi, Marco; Fontanini, Gabriella (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2023)
Among non-small cell lung cancers (NSCLCs), sarcomatoid carcinomas account for 3%. They are rare tumours with a poor prognosis, classified into three subgroups, namely pleomorphic carcinoma, pulmonary blastoma and carcinosarcoma. In the 5th edition of WHO Classification of Thoracic Tumours more space is given to SMARC4-deficient lung cancers. Although studies on SMARCA4-deficient lung tumours are limited, a small percentage of SMARCA4 loss is present within NSCLCs. This finding is clinically relevant, as the loss of the SMARCA4 gene is associated with a worse prognosis. In our study, we analysed the presence of the main catalytic subunit of the SMARCA4 gene, the BRG1 protein, in 60 sarcomatoid lung tumours. The results of our study show that 5.3% of sarcomatoid carcinomas have BRG1-loss in tumour cells, proving that a non-negligible amount of lung sarcomatoid carcinomas are SMARCA4-deficient. These data open the debate on the necessity of including the detection of SMARCA4 within a standardised immunohistochemical panel.